American drug index - Billups, Norman; Billups, Shirly M. (St. Louis, Missouri : Facts and Comparisons, 2003)
Rigorously updated for 2004, this reference contains more than 22,000 entries and represents a complete and current listing of drugs and drug products available in a single source.
Monographs -- Standard medical abbreviations -- Calculations -- Common systems of weights and measures -- Approximate practical equivalents -- International system of units -- Normal laboratory values -- Trademark glossary -- Medical terminology glossary -- Container requirements for USP26/NF 21 compendial dosage forms and nutritional supplements -- Container and storage requirements for sterile USD 26 dosage forms -- Oral dosage forms that should not be crushed or chewed -- Drug names that look alike and sound alike -- Recommended childhood immunization schedule -- FDA pregnancy categories -- Controlled substances summary -- Radio-contrast media -- Radio-isotopes -- Pharmaceutical company labeler code index -- Pharmaceutical manufacturer and drug distributor listing.
Keywords: DRUGS -- DICTIONARIES